2020
DOI: 10.32598/jccnc.6.3.338.1
|View full text |Cite
|
Sign up to set email alerts
|

Measuring Cultural Competence in Nursing: A Review Study

Abstract: Background: Cultural competence is an essential factor in providing effective services to care seekers. Providing cultural care is a necessity in nursing; thus, measuring cultural competence in nurses is of great importance. Accordingly, the current study aimed at introducing the scales for measuring cultural competence in nursing. Methods: The current narrative review study was conducted by searching the internet and library resources through credible databases. The keywords “cultural competence, cultural co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 44 publications
1
3
0
Order By: Relevance
“…Likewise, another study reported that achievement was a motivating factor in the workplace [7]. According to the findings of another study, nursing staff considered achievement to be the most important motivational factor [40,41]. According to the interpretation of the present findings, it can be concluded that nurses' motivation in this dimension was high due to their feeling of being valuable and useful in saving a person's life.…”
Section: Discussionsupporting
confidence: 55%
“…Likewise, another study reported that achievement was a motivating factor in the workplace [7]. According to the findings of another study, nursing staff considered achievement to be the most important motivational factor [40,41]. According to the interpretation of the present findings, it can be concluded that nurses' motivation in this dimension was high due to their feeling of being valuable and useful in saving a person's life.…”
Section: Discussionsupporting
confidence: 55%
“…Cultural competence is a fundamental skill for nurses in delivering culturally congruent care [ 1 ], and it represents the process by which nurses demonstrate an understanding of and sensitivity to the cultural background of their patients a. It is a nurse’s capacity to improve the health and well-being of clients whose cultural backgrounds are different from their own [ 3 ]. Cultural competence is also essential for nursing students and nurse educators in all learning-teaching approaches [ 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…Comparing the results of this study with other questionnaires designed to assess cultural competence, we concluded that despite many questionnaires and scales being developed to assess cultural competence, only some had been developed based on a particular model or theory. Moreover, some of these scales include a great number of items that affect the applicability of those scales (Naghizadeh et al., 2020; Yadollahi, Ebadi, & Asadizaker, 2020; Yadollahi, Ebadi, MolaviNejad, et al., 2020). For example, the Cultural Competence Health Practitioner Assessment scale has 67 items, and the Transcultural Self‐Efficacy Tool (TSET) has 83 items (Jeffreys & Smodlaka, 1996; Osmancevic et al., 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Numerous attempts have been made to develop cultural competency scales. Although they have been used in different studies on cultural competence, there is insufficient information about the psychometric properties of some of these scales (Osmancevic et al., 2020 ; Yadollahi, Ebadi, & Asadizaker, 2020 ; Yadollahi, Ebadi, MolaviNejad, et al., 2020 ). For example, some scales do not cover all the essential components of cultural competence, and some others have not been specifically designed for nurses.…”
Section: Introductionmentioning
confidence: 99%